The knowledge and skill of registered nursing staff at Chris Hani Baragwanath Academic Hospital Emergency Units on endotracheal tube cuff manometry, before and after a training session - Henning, Jandre (University of the Witwatersrand, Johannesburg, 2022)
Introduction Appropriate management of endotracheal tube (ETT) cuff pressures is essential to prevent patient morbidity and mortality. Due to increased length of stay of critically ill patients in emergency departments (EDs), it has become an increasingly important skill among registered nurses. Methods This prospective longitudinal interventional study was performed among registered nurses (RNs) at Chris Hani Baragwanath Academic Hospital’s EDs. The study aimed to determine their current knowledge and practical skills on ETT cuff manometry and assess the effectiveness of a training program. The training program involved theoretical and practical components. RNs theoretical knowledge was assessed with a pre- and post-training questionnaire. Theoretical and practical scores were compared pre- and post-training Results Of the 63 RNs employed in the ED, 95% (60 RNs) participated in this study. Only 38.9% used cuff manometry as standard practice and only 12.8% are checking it at appropriate 12 hourly intervals. The pre-training median score on theory was 4.5 (IQR=3.0) and improved to 7.0 (IQR=3.0) post-training. The maximum achievable score was 11 with a pre-training average of 41.8% and post-training of 64.5% (p=0.001). The practical pre-training median score was 1.0 (IQR=8.0) and improved to 12.0 (IQR=2.0) post-training. The maximum achievable score was 12 with a pre-training average of 29.1% and a post-training average of 93.3% (p=0.001). Conclusion This study showed the current lack of knowledge and skills on endotracheal cuff pressure manometry among emergency RNs. It also correlates with other evidence that supports the need for ongoing training programs. Our training program led to significant improvement among participants in both knowledge and practical skills. This training program was well received by participants and deemed to be practice changing. The recommendation after this study will be for South African emergency units to consider using this study and training material as a guide for annual in-service training
A Research Report submitted in partial fulfillment of the requirements for the degree of Master of Medicine in Emergency Medicine to the Faculty of Health Sciences, School of Clinical Medicine, University of Witwatersrand, Johannesburg 2022
Keywords: Endotracheal tube; Cuff manometry; Emergency nursing; UCTD; SDG-3: Good health and well-being